Study on 3′-UTR length polymorphism in peripheral blood mononuclear cells of uremia patient. (2nd January 2016) - Sui, Weiguo; Zheng, Can; Yang, Ming; Ou, Minglin; Chen, Jiejing; Dong, Li; Chen, Peng; Hou, Xianliang; Liu, Fuhua; Wei, Xiaolian; Dai, Yong
Abstract: Objective : The objective of this study was to measure the 3′-untranslated region (3′-UTR) polymorphism lengths in peripheral blood mononuclear cells (PBMCs) from uremia patients. Method : We sequenced the alternative polyadenylation sites in the 3′-UTR of PBMCs from 10 uremic patients and 10 healthy people to detect different gene expression levels between uremia patients and healthy controls. Quantitative reverse transcription polymerase chain reaction was used as validation. Result : Compared with the healthy control group, 691 genes in uremic patients had significantly different 3′-UTR lengths. Of these genes, 475 genes showed shortened 3′-UTRs, and the 3′-UTRs of 216 genes were lengthened. The verification results matched the original sequencing results. Conclusion : There were significant differences in 3′-UTR lengths between uremic patients and healthy controls, and analysis of the differential genes may contribute to the understanding of uremia pathogenesis.